2017
DOI: 10.21462/ijefll.v2i2.39
|View full text |Cite
|
Sign up to set email alerts
|

BBC Radio Drama Series Cabin Pressure: Abu Dhabi for Giving Listening Exposure to Students: A View from Humour Perspective

Abstract: Using authentic materials to give listening exposure is essential to improve English language learners’ listening skill and using radio is one way to do so. To reduce anxiety in listening, choosing humorous material can be done as humour has been proven beneficial in classroom context, for example, in reducing stress. Using the partial result of a study conducted by the same author and completed by library study about ethics of using humour in the classroom, this study is to investigate whether verbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Many problems in mastering the English listening skill (Sayuri, 2016) whrere the English teachers need to think on how to improve the quality of the students' listening skill (Putri, et al, 2018). Many ways to improve the students' listening skill, such as using BBC Radio (Cendra, 2017), youtube, or songs (Lestary & Seriadi, 2019).…”
Section: The Use Of English Songs In Efl Teachingmentioning
confidence: 99%
“…Many problems in mastering the English listening skill (Sayuri, 2016) whrere the English teachers need to think on how to improve the quality of the students' listening skill (Putri, et al, 2018). Many ways to improve the students' listening skill, such as using BBC Radio (Cendra, 2017), youtube, or songs (Lestary & Seriadi, 2019).…”
Section: The Use Of English Songs In Efl Teachingmentioning
confidence: 99%
“…For instance, in term of listening skill, El Meysarah (2015) found that listening ability of state university of Surabaya students is good enough, meanwhile in Riau university, listening ability of Riau university students is still low (Ristanti, et al, 2016). Some efforts have been implemented by the English teachers and lecturers to cope the problems of listening skill of the English learners (Afsharrad & Nafchi, 2015;Samawiyah & Saifuddin, 2016;Hanafi, 2016;Cendra, 2017) There have been numerous attempts to describe listening comprehension in terms of taxonomies of sub-skills. This approach is based on the notion that these skills underlie the process, and the act of listening consists of the application of various separate skills (Barta, 2010).…”
Section: Introductionmentioning
confidence: 99%